Sinergi Antara Prinsip Konstitusi Hijau dan Praktik Demokrasi Hijau Implikasi Hukum untuk Keberlanjutan Lingkungan - Muhammad Khaidir Kahfi Natsir; Nurul Chaerani Nur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This paper discusses in depth the relationship between green constitution and green democracy in the context of environmental protection in Indonesia. In the modern era, environmental issues have become increasingly urgent, especially with the growing threats to ecosystems due to human activities. This research raises several problems, including the lack of public understanding regarding environmental legal norms contained in the 1945 Constitution, as well as the challenges faced in its implementation. The main objective of this research is to explore and analyze the connection between the principles of green constitution as stipulated in Article 28H paragraph (1) and Article 33 paragraph (4) of the 1945 Constitution with the existing environmental policy practices. This study also aims to identify the dynamics influencing the development of environmental protection law in Indonesia and to assess the effectiveness of the policies that have been implemented. The method used in this research is a normative juridical approach with descriptive analysis. Through a systematic literature review, this study examines various legal sources, official documents, and relevant literature related to the theme of green constitution and environmental protection. The findings indicate that although environmental norms have been accommodated in the constitution, significant challenges remain in terms of implementation, including the misalignment between government policies and constitutional mandates. This research concludes that to achieve optimal environmental protection goals, continuous evaluation and oversight of the implementation of existing laws are necessary. Furthermore, closer collaboration between the government, society, and other stakeholders is crucial to ensure that the policies adopted are not merely symbolic but also effective in protecting the environment. Moreover, this study emphasizes the importance of integrating the concept of ecocracy into public policy, which can serve as a guideline in making environmentally conscious decisions. Thus, the protection and management of the environment can be effectively and sustainably realized, creating a safe and healthy environment for future generations.